Practice perspectives and theoretical debates about social workers' legal powers to protect adults. (January 2020) - Stevens, Martin; Manthorpe, Jill; Martineau, Stephen; Norrie, Caroline
Summary: This paper explores arguments for and against increasing social workers' legal powers in adult protection (safeguarding) in England, where there is no direct power of entry. It draws on a research study conducted in 2016–17 involving an international literature review, interviews with social workers (n = 22), managers (n = 15), older and disabled people (n = 6) and carers (n = 5) and a survey of adult safeguarding managers (n = 27). The paper contextualises findings by exploring concepts of vulnerability and autonomy. Findings: Most participants were in favour of increased powers for social workers undertaking safeguarding enquiries. A power of entry was seen to strengthen the legal basis of safeguarding and provide legitimacy for social workers to act. However, many participants expressed reservations, arguing that cases could generally be resolved with good social work, there would be a risk of negative impact on adults at risk and their families, the power of entry conflicted with social work practice and values and it could negatively affect social work relationships. Such arguments indicate a nuanced view of autonomy and vulnerability, which allow for doubt about the autonomy of people with capacity in certain circumstances. Applications: The paper suggests the need for investment in the processes of implementation of risk management if increased legal powers are introduced. There could be a value in encouraging social workers to make explicit their assumptions about the definitions of vulnerability and its impact on autonomy and to explore the subjective experience of vulnerability in their judgements about intervening in these kinds of situations.